What Makes a Corner a Corner? - Wallace, John; Pearson, Jennifer (Teaching children mathematics, 1998)
The group of grade-3 boys enthusiastically grabbed the box of blocks and headed for their desks. The boys had been waiting three days for their turn to use the blocks. I had let them play with the blocks before school or if they mate privilege.